NK/T-cell lymphoma of the nasal cavity: an unexpected diagnosis. Issue 3 (24th March 2021) - Manole, Constantin; Farrell, Eric; Lang, Emer
Abstract : Nasal-type Natural Killer/T-cell Lymphoma (NKTL) is a rare form of extranodal non-Hodgkin's lymphoma, typically arising in the nasopharynx and displaying an aggressive and ultimately fatal clinical course. The disease is linked to Epstein-Barr virus infection and is endemic to Asia and South America, but extremely few cases have been reported in Europe. We present two cases of nasal NKTL unexpectedly diagnosed in elderly patients, following very different presentations to our otolaryngology service. The first case is that of a 73-year-old Irish man with recurrent nasal vestibulitis despite antibiotic treatment. The second case involves a 79-year-old Irish woman presenting with a large mass on the hard palate, found to invade into the floor of the nose. NKTL can pose diagnostic challenges, as the initial clinical presentation can be non-specific and overlap with other nasal conditions, leading to a delay in diagnosis. Biopsy with histopathological and immunohistochemistry analysis is required to establish the definitive diagnosis. Treatment involves multidisciplinary input from radiotherapy and medical oncologists. Clinicians must be aware of this disease and have an index of suspicion when dealing with persistent or aggressive nasal conditions.